Hydroponic production of vegetables in Malaysia using the nutrient film technique - Lim, E. S. (International Society for Soilless Culture, 1986)
The production of vegetables using insulated NFT troughs vas studied. Various leaf and fruit vegetables were successfully grown and good yields obtained. The NFT troughs were easy to manage, had low labour requirements and may be used for cropping continuously. The troughs may be constructed out of polystyrene boards or wood. The NFT trough system is simple and cheap to build and could be used on a small scale by the home gardener or on a large scale by commercial growers.